Developing a COVID-19 emergency airway team. Issue 4 (7th November 2020) - Mehta, Arpan; Aziz, Michael F.
Abstract : The COVID-19 disease pandemic has changed the world of medicine as we know it, with inevitable long-standing repercussions. The impact to the anesthesiologist is profound, resulting in modification to multiple areas of practice. With the high contagiousness of the disease from droplets, but also aerosolization being a significant factor, the whole process of airway management carries significant risk to the health care provider. During troubled times, response teams for acute events are often developed. We focus this short piece on the development and implementation of an airway response team for COVID-19 patients.